2008
DOI: 10.1021/ic800863z
|View full text |Cite
|
Sign up to set email alerts
|

BX4 and AlX4 Superhalogen Anions (X = F, Cl, Br): An ab Initio Study

Abstract: The vertical electron detachment energies (VDEs) of 30 MX 4 (-) (M = B, Al; X = F, Cl, Br) anions were calculated at the OVGF level with the 6-311+G(3df) basis sets. The largest vertical electron binding energy was found for the AlF 4 (-) system (9.789 eV). The strong VDE dependence on the symmetry of the species, ligand type, ligand-central atom distance, and bonding/nonbonding/antibonding character of the highest occupied molecular orbital was observed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
69
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 34 publications
5
69
1
Order By: Relevance
“…5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Along with the deepening of the related researches, it has been a Author to whom correspondence should be addressed. Electronic mail: rayinyin@nwu.edu.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Along with the deepening of the related researches, it has been a Author to whom correspondence should be addressed. Electronic mail: rayinyin@nwu.edu.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic mail: rayinyin@nwu.edu. indicated that the VDEs of superhalogens could be improved both by strengthening the electronegativity of the ligand 12,16,20,23,[27][28][29][30][31] and by increasing the number of ligands. 10,11,29,30,[32][33][34] 8,42,43 have been utilized to design new superhalogens recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,20] Along with the growing interest in the design and synthesis of new superhalogens, these studies have been extended to systems composed of transition-metal atoms [28,[30][31][32][33] or even hydrogen [34] at the center surrounded with halogen or oxygen [35][36][37] as ligand atoms. Furthermore, superhalogens that contain more than one metal atom, such as Na x Cl x+1 (x = 1-4), [38] Ta 3 F 16 -, [19] and Mg 2 F 5 , [39] have also been found.…”
Section: Introductionmentioning
confidence: 99%
“…Such interhalogens are good halogenating agents, but there is almost no data on mixed species. Only Skurski's group [20,21] has investigated Na-, B-, and Al-based complexes that contain mixed halogen atoms as ligand. This lack of data has motivated us to take a closer look at the various iron-based clusters that contain chlorine, bromine, and interhalogen compounds to explore new magnetic superhalogens.…”
Section: Introductionmentioning
confidence: 99%